Pengaruh Struktur Aktiva, Operating Leverage, Beban Pajak, dan Laba Ditahan terhadap Struktur Keuangan pada PT. Tona - Desy Putri Sari; Thomas Sumarsan Goh; Elidawati Elidawati; Edison Sagala (Ekonomis: Journal of Economics and Business, 2022)
His study aims to examine whether the financial structure is influenced by asset structure, operating leverage, tax expense, and retained earnings at PT. Tona. The results of this study reveal that the structure of assets, operating leverage, tax expense, and retained earnings all affect the financial structure